Alienation - a long-overlooked concept of relevance to social work? - Henrik Skovlund (Social Work and Society, 2019)
Alienation is seemingly a relevant concept in social work in so far as this concerns marginalized and vulnerable groups of people. Nevertheless, the interest in alienation theory has declined within social science as a whole, partly due to postmodern turns to discrimination and marginalization. This paper revisits significant theories on alienation to clarify the status of alienation theory in theory and practice within social work. Two main perspectives will be suggested to classify alienation theory: the perspective of those to whom alienation is an omnipresent phenomenon that characterizes modern society in general, and those to whom alienation primarily signifies experiences of discrepancy between oneself and society such as powerlessness, meaninglessness and loneliness. Thus, the paper will trace the development from the broad characterizations of alienation, inspired by theories such as those of Rousseau and Marx, to theories that favour phenomenological and empirical approaches to alienation. At the end of the paper, the two perspectives will be discussed in relation to an example of applied usage of alienation theory in social work to clarify the status of alienation theory in social work with vulnerable groups of society.